NTRU binary polynomials parameters selection for reduction of decryption failure - Gaithuru, Juliet Nyokabi (SPRINGER VERLAG, 2017)
This paper studies the NTRU public key cryptosystem to identify the most influential parameters for decryption failure confirming that decryption failure is key-dependent. The study uses binary polynomials and analyzes the correlation between the parameter sets recommended in the EESS 1v2 (2003) and Jeffrey Hoffstein et al. (2003). The observed relationships are then used to recommend an extended parameter selection criteria which ensures invertibility and reduced probability of decryption failure. We then recommend a condition for selecting an appropriately large size of q which is the least size required for ensuring successful message decryption. The study focuses on binary polynomials as it allows for a smaller public key size and for the purpose of providing better insights leading to further study into other variants of NTRU.